2022
DOI: 10.7717/peerj.13980
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis and physiological characteristics of exogenous naphthylacetic acid application to regulate the healing process of oriental melon grafted onto squash

Abstract: The plant graft healing process is an intricate development influenced by numerous endogenous and environmental factors. This process involves the histological changes, physiological and biochemical reactions, signal transduction, and hormone exchanges in the grafting junction. Studies have shown that applying exogenous plant growth regulators can effectively promote the graft healing process and improve the quality of grafted plantlets. However, the physiological and molecular mechanism of graft healing forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The plant hormones IAA, CTK, and GAs, were closely related to callus formation, vascular bundle development, and reconnection during the graft union healing process [41][42][43]. Some reports showed that applying exogenous naphthylacetic acid (NAA) could significantly promote graft union formation [44]. It has been reported that several essential genes play a role in regulating graft union healing.…”
Section: Discussionmentioning
confidence: 99%
“…The plant hormones IAA, CTK, and GAs, were closely related to callus formation, vascular bundle development, and reconnection during the graft union healing process [41][42][43]. Some reports showed that applying exogenous naphthylacetic acid (NAA) could significantly promote graft union formation [44]. It has been reported that several essential genes play a role in regulating graft union healing.…”
Section: Discussionmentioning
confidence: 99%